Analysis of Effectiveness of Mutual Muraja'ah on Juz Amma Reading Fluency for Kindegarten Class at TPQ Raudlatul Qur'an Karang Duwak Arosbaya - Hasan , Mushohihul; Faizin , Faizin; Putra , Holil Baita (LPPPM STAI Darul Hikmah Bangkalan, 2021)
In this study, the researcher raised a learning method problem namely mutual Muroja’ah to read juz amma fluently for kindergarten students at TPQ Raudlatul Qur’an. In this study, researcher used a qualitative descriptive research approach with case study research. The data collection techniques used observation, test, interview and documentation. The analysis techniques used were a) data reduction, b) data display and c) conclusion making. As the result of the study are: a) the mutual muroja’ah method implementation was conducted by many ways such as guided muroja’ah, continuing verse muroja’ah and reading together, b) the method is very effective in helping students to read Alqur’an fluently, in terms of the results of evaluation test every three months that the percentage assessment result show that many students obtain grade B and even some students achieved grade A in terms of reading fluency